# Find f(x) if f'(x)= #(e^(2x) +4e^-x)/e^x# and f(ln2)=2. Do u just find the anti-derivative for numerator and denominator separately?

No you can't do it that way.

The derivative of a quotient is not just the quotient of the derivatives, so, likewise, the anti derivative of a quotient is not just the quotient of antiderivatives..

In general, finding antiderivatives is much harder than finding derivatives. (In fact some antiderivatives cannot be nicely expressed.)

Noe way to find the antiderivative of

is to rewrite it.

Now, the antiderivative of a sum is just the sum of the antiderivative (just as the derivative of a sum is he sum of the derivatives).

So,

(Check the answer by differentiating.)

By signing up, you agree to our Terms of Service and Privacy Policy

To find ( f(x) ), integrate ( f'(x) ) with respect to ( x ), ensuring to apply the initial condition ( f(\ln 2) = 2 ). You can separately integrate the numerator and denominator and then divide the results. Therefore,

[ f(x) = \frac{{\int (e^{2x} + 4e^{-x}) , dx}}{{\int e^x , dx}} ]

Integrating the numerator:

[ \int (e^{2x} + 4e^{-x}) , dx = \frac{1}{2} e^{2x} - 4e^{-x} + C_1 ]

Integrating the denominator:

[ \int e^x , dx = e^x + C_2 ]

Dividing the results:

[ f(x) = \frac{\frac{1}{2} e^{2x} - 4e^{-x} + C_1}{e^x + C_2} ]

Using the initial condition ( f(\ln 2) = 2 ):

[ 2 = \frac{\frac{1}{2} e^{2\ln 2} - 4e^{-\ln 2} + C_1}{e^{\ln 2} + C_2} ]

[ 2 = \frac{\frac{1}{2} \cdot 2^2 - 4 \cdot 2^{-1} + C_1}{2 + C_2} ]

[ 2 = \frac{2 - 2 + C_1}{2 + C_2} ]

[ 2 = \frac{C_1}{2 + C_2} ]

[ 4 + 2C_2 = C_1 ]

Substituting back into ( f(x) ):

[ f(x) = \frac{\frac{1}{2} e^{2x} - 4e^{-x} + (4 + 2C_2)}{e^x + C_2} ]

[ f(x) = \frac{1}{2} e^{x} - 4e^{-x} + 2 + C_2 ]

Therefore,

[ f(x) = \frac{1}{2} e^{x} - 4e^{-x} + 2 + C_2 ]

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you differentiate #1/cos(x) = x/(x-y^2-y)#?
- How do you use the chain rule to differentiate #y=(-3x^5+1)^3#?
- How do you differentiate #e^sqrt(xy)-sqrt(xy)=8#?
- How do you differentiate #f(x)=cos(3x)*(2/3tanx)# using the product rule?
- How do you use the chain rule to differentiate #y=(2x^3+7)^6(2x+1)^8#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7